Importance of Consumer Satisfaction to Improve Consumer Trust LinkAja Digital Wallet - Evelyn Wijaya; Yusnita Octafilia (Kusuma Negara Business School, 2021)
Currently, digital wallets in Indonesia continue to see an increase in the number of users. In general, digital wallets are preferred for online transactions over other payment methods. This study aims to analyze the effect of ease of use and brand image on consumer satisfaction and trust in LinkAja digital wallet. The population in this study was users of LinkAja in Pekanbaru. The samples were 150 respondents obtained using Accidental Sampling technique. Data analysis technique used was Structural Equation Model (SEM) with the help of Smart PLS 3.0. The results show that ease of use and brand image positively and significantly affect consumer satisfaction and trust and consumer trust positively and significantly affects consumer trust. Therefore, companies are encouraged to provide digital wallet features that promote user’s ease and comfort.